Increased FDG uptake in AF individuals suggesting atrial inflammation visualized by FDG PET/CT with glucose uptake suppression protocols. (14th October 2021) - Kupusovic, J; Weber, M; Kessler, L; Pesch, E; Riesinger, L; Wakili, R; Dobrev, D; Rischpler, C; Rassaf, T; Siebermair, J
Abstract: Background: Pathophysiology of atrial fibrillation (AF) is multifactorial. Attention has been drawn towards atrial inflammation underlying arrhythmogenic remodeling. The aim of our study was to evaluate if a specific preparation protocol for positron emission tomography/computed tomography (PET/CT) with 18Fluor-labelled fluorodeoxyglucose (18F-FDG) was capable of detecting atrial hypermetabolism as surrogate for inflammation in AF, with the specific hypothesis that protocols specifically aiming to suppress physiologic glucose metabolism (fasting protocols: inflammation and malignancy preparation) were superior to non-fasting protocols. Methods: We conducted a single-center study including n=75 patients with a history of AF and n=75 controls without AF (matched for age, sex and left ventricular systolic function) undergoing three different preparation protocols (each n=25 per group): i.) inflammation, ii.) malignancy and iii.) viability protocol before 18F-FDG-PET/CT. We performed visual analysis of local detectable atrial uptake (figure 1A) and assessed quantitative uptake in predetermined loci of the atria and endocrine adipose tissue (EAT), using maximum standardized uptake values (SUVmax) and target to background ratios (TBR). Results: Our analysis of visual atrial 18F-FDG uptake revealed that atrial uptake was exclusively observed in AF patients using the malignancy (13/25 patients) and inflammation (10/25 patients) protocol, while the viability preparation revealed atrial uptake both in AF (n=6 patients) and non-AF patients (n=5 patients). With respect to quantitative measures between AF and non-AF individuals using the inflammation protocol, patients with AF showed significantly higher uptake values in the right atrium (SUVmax: 2.54±0.75 vs. 2.03±0.66, p=0.01); TBR 1.51±0.44 vs. 1.18±0.20, p<0.01), right atrial appendage (SUVmax: 2.44±0.71 vs. 2.02±0.64, p=0.03; TBR: 1.47±0.47 vs. 1.20±0.26, p=0.02) and also in EAT (SUVmax: 1.39±0.46 vs. 1.13±0.40, p=0.04), figure 1B. Despite a trend of higher tracer uptake related to the presence of AF in left atrial structures, no statistical significances could be observed between AF and non-AF individuals. Conclusion: This retrospective study demonstrates that protocols specifically designed to suppress physiologic glucose uptake seem to be superior in detecting atrial FDG uptake, which could be indicative of atrial inflammation in AF patients. Based on our results the right atrium seems to be more affected from these changes. These results point towards a potential role of right atrial inflammatory processes in AF pathophysiology besides the established left atrial ectopic triggers. Funding Acknowledgement: Type of funding sources: None.